Artificial Intelligence-Driven 3D Modeling: Transformative Applications Analysis - Rao, Kunliang (Transactions on Computer Science and Intelligent Systems Research, 2025)
The convergence of Artificial Intelligence (AI) and 3D modeling technologies profoundly changes several key industries. This study analyzes the innovative applications and practical value of AI-powered 3D modeling technology in four major fields: architecture, education, healthcare, and gaming. First, AI technology optimizes design solutions in the construction industry through intelligent algorithms to significantly improve buildings’ functionality, energy efficiency, and structural stability. Combined with BIM systems, AI can detect and resolve design conflicts in advance. High-precision 3D digital reconstruction is realized through laser scanning and deep learning for historic building preservation. Meanwhile, 3D modeling technology visualizes abstract knowledge, and virtual anatomical models and historical scene restoration greatly enhance the teaching effect. The AI-driven adaptive learning system analyzes student data and intelligently adjusts the teaching content and rhythm, effectively improving learning efficiency. AI-based medical image 3D reconstruction technology realizes the precise positioning of lesions. Virtual surgery simulation systems and personalized bone substitute designs enhance surgical safety and fitness. The gaming industry utilizes AI to achieve efficient content generation. Deep learning technology makes character behavior more realistic and natural, dramatically improving player immersion. Despite its promising future, the technology still faces data quality, model generalization, and real-time performance challenges. In the future, it is necessary to promote AI and 3D modeling technology from the laboratory to industrial applications by developing cross-industry universal models, optimizing edge computing technology, and improving human-machine collaboration mechanisms.